Intravitreal Fluocinolone Acetonide Implant (ILUVIEN®) for the Treatment of Retinal Conditions. A Review of Clinical Studies - Mushtaq Y; Mushtaq MM; Gatzioufas Z; Ripa M; Motta L; Panos GD (Dove Medical Press, 2023)
Yusuf Mushtaq,1,* Maryam M Mushtaq,2,* Zisis Gatzioufas,3 Matteo Ripa,4 Lorenzo Motta,5 Georgios D Panos1 1Department of Ophthalmology, Queen's Medical Centre, Nottingham University Hospitals NHS Trust & School of Medicine, University of Nottingham, Nottingham, UK; 2Department of Acute Medicine, Luton and Dunstable University Hospitals NHS Trust, Luton, UK; 3Department of Ophthalmology, Basel University Hospital & University of Basel School of Medicine, Basel, Switzerland; 4Ophthalmology Unit, "Fondazione Policlinico Universitario A. Gemelli IRCCS", Rome, Italy; 5Department of Ophthalmology, William Harvey Hospital, East Kent Hospitals University NHS Foundation Trust, Kent, UK*These authors contributed equally to this workCorrespondence: Georgios D Panos, Department of Ophthalmology, Queen's Medical Centre, Derby Road, Lenton, Nottingham, NG7 2UH, UK, Tel +44 115 924 9924, Email gdpanos@gmail.com Lorenzo Motta, Department of Ophthalmology, William Harvey Hospital, Kennington Road, Willesborough, Ashford, Kent, TN24 0LZ, UK, Tel +44 1233 633331, Email lorenzo.motta@nhs.netAbstract: Fluocinolone acetonide (FAc) intravitreal implant (Iluvien®) is a corticosteroid implant indicated for the treatment of diabetic macular oedema (DMO) in patients who have previously received conventional treatment without good response, non-infectious posterior uveitis, and as an off-label treatment of the macular oedema secondary to retinal vein occlusion. FAc is a non-biodegradable 0.19 mg intravitreal implant which is designed to release FAc over 3 years at a rate of approximately 0.2 mcg per day. The aim of this review is to describe the special pharmacological properties of Iluvien and display the outcomes of the most important clinical trials and real-world studies regarding its efficacy and safety for the management of the above retinal disorders.Keywords: Iluvien, steroid implant, diabetic macular oedema, intravitreal implant, posterior uveitis, retinal vein occlusion